Exclusive breastfeeding in COVID-19 pandemic times: integrative review (Research, Society and Development, 2021)
Introduction: Exclusive breastfeeding (EBF) is seen as one of the priority lines of care in Public Health as strategies to reduce child mortality worldwide. The transmission of the corona-virus occurs, according to epidemiology, horizontally, from person to person, by direct or indirect contact with contaminated secretions generated when speaking, sneezing or coughing, and by contact with surfaces contaminated with the virus and later with the touch mucous membranes of the nose and mouth. When exclusive breastfeeding is contextualized with the new pandemic scenario caused by the current outbreak of the corona-virus (SARS-CoV-2), it still presents itself as an unknown factor, with no study proving transmission through breast milk. Methods: Refers to an integrative literature review using electronic databases as the source of information. Results: The article was built based on the guidelines of the PreferredReportingItems for Systematic Reviews and Meta-Analyzes (PRISMA) methodology. Discussion: There is no scientific evidence that the virus is transmitted vertically through breast milk. Considering the countless benefits of breastfeeding, which outweigh the risks of COVID-19 in this population, breastfeeding must be properly guided, regardless of whether the mother is asymptomatic, suspected or confirmed of the disease. Final considerations: Educational and preventive actions related to breast complications are necessary and appropriate issues to support the physiological breastfeeding process in the face of the pandemic.